(untitled) (Global Journals of Research in Engineering, 2013)
Two main problems in wireless communications are, limited available spectrum and inefficiency in the spectrum allocation policy. These problems lead to the blocking of both initial and hand-off calls. Cognitive radio (CR) offers solution by utilizing the spectrum holes in space without introducing an unacceptable fear of harmful interference for the primary user and also solves the spectrum inefficiency and spectrum scarcity problem. Spectrum allocation scheme is proposed in two phases. In the first phase, a collision between two calls for spectral band allocation is resolved. In second phase, spectral band allocation among a number of calls is considered. The main objective is to minimize the forced termination of hand-off calls and to achieve opportunistic spectrum channel allocation by assigning different priority levels to different calls.